2014
DOI: 10.1007/s10719-014-9555-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum sulfatide and carotid intima media thickness in patients with familial hypercholesterolemia

Abstract: There is a positive association between sulfatide and atherosclerosis in an animal model for human familial hypercholesterolemia. Carotid intima–media thickness (IMT) is thought to be a marker of atherosclerosis in humans. We investigated the relationship between sulfatide and carotid IMT in heterozygous familial hypercholesterolemia (FH) patients. Thirty-five genetically-verified heterozygous patients with FH and 34 healthy controls were recruited into our study. We measured serum sulfatide levels, the caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Meanwhile severe blood lipid loss may partly contribute to low serum sulfatides in patients. However, in patients with atherosclerosis, we and other studies found a positive correlation between serum sulfatide levels and human atherosclerotic lesions formation 12, 20) . Current study suggested that sulfatides also are involved in the late stage of severe coronary atherosclerosis, even the prognosis of STEMI.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Meanwhile severe blood lipid loss may partly contribute to low serum sulfatides in patients. However, in patients with atherosclerosis, we and other studies found a positive correlation between serum sulfatide levels and human atherosclerotic lesions formation 12, 20) . Current study suggested that sulfatides also are involved in the late stage of severe coronary atherosclerosis, even the prognosis of STEMI.…”
Section: Discussioncontrasting
confidence: 52%
“…Studies have also demonstrated that sulfatides specifically bind to extracellular matrix components, such as thrombospondin, laminin, and von Willebrand factor 19) . The release of sulfatides from the surface of the neutrophils and in combination with an increased expression of P-selectin on the surface of platelets led to the accumulation of cytokines and the extracellular matrix in vessel lesions, resulting in increased vascular wall thickness 20, 21) .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that serum sulfatides in the lipoprotein particles may prevent coagulation/thrombogenesis by interrupting the sulfatides-P-selectin interaction in platelet adhesion and aggregation [18]. Therefore, we had focused on the association between serum sulfatide levels and cardiovascular disease (CVD)-related vascular thrombosis in previous studies [19][20][21]. We reported a significant association between serum sulfatide levels and CVDs in hemodialysis patients who were at high risk of developing CVDs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Leukocytes then adhere firmly to the vessel surface through leukocyte Mac-1 via direct attachment to platelet receptors [17]. It has been known that sulfatides are expressed on the membrane surface of, and are also excreted by, neutrophils [18,19]. Since neutrophil activation occurred after stent deployment [20], lots of sulfatides were released from activated neutrophils.…”
Section: In Inflammatory Reactionmentioning
confidence: 99%